2019
DOI: 10.1111/jfpp.13888
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of leaf and bark cinnamon essential oils against Listeria monocytogenes and Salmonella typhimurium in broth system and on celery

Abstract: Cinnamon essential oils (CEOs) from leaf and bark were investigated for their antimicrobial potential against Salmonella typhimurium and Listeria monocytogenes. Minimum inhibitory concentration of leaf and bark CEOs against S. typhimurium and L. monocytogenes at low (4‐log CFU/ml) and high (9‐log CFU/ml) initial concentrations was 0.5% (vol/vol). When applied on fresh celery previously inoculated with S. typhimurium or L. monocytogenes, 0.5% leaf and bark CEOs significantly reduced (p < 0.05) the growth of S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…It was determined that EOs of the leaf and bark can be used as a potential antimicrobial agent in foods. EO derived from bark was better than those derived from leaf with respect to antimicrobial activity . Other researchers confirmed that the amount of bark EOs in cinnamon was high …”
Section: Plant‐based Preservativesmentioning
confidence: 92%
“…It was determined that EOs of the leaf and bark can be used as a potential antimicrobial agent in foods. EO derived from bark was better than those derived from leaf with respect to antimicrobial activity . Other researchers confirmed that the amount of bark EOs in cinnamon was high …”
Section: Plant‐based Preservativesmentioning
confidence: 92%
“…Listeria is responsible for about 1600 cases of food poisoning in the US and 260 deaths annually, while Salmonella caused about 19,000 hospitalizations and 380 deaths annually in the US. Both Salmonella and Listeria can contaminate food, such as fruits, vegetables, seafood, and dairy products [6]. Furthermore, Brnawi et al [6] investigated whether the cinnamon EO would inhibit the growth of bacteria growing on celery stored at 4 °C for 7 days.…”
Section: Description Of Eosmentioning
confidence: 99%
“…Humans have used EOs for thousands of years, not only as ingredients of perfumes or as seasonings for the aromatization of food, but also in folk medicine, because of their many different biological properties, including antimicrobial properties [6]. The antimicrobial qualities are essential in managing the rapidly growing issue of drug-resistant microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, the limitation of a singular EO treatment in the efficiency has been highlighted, as reported by previous studies, mainly because of: (1) The negligible antibacterial effects (ca. <1 log reduction) [25,44,45], (2) the requirement of a high EO concentration to achieve a desirable effect from short-term exposure [46,47], or (3) the requirement of a long-term exposure [48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Eos As Antimicrobial Agentsmentioning
confidence: 99%